A case of metastatic adenoid cystic (basal cell) carcinoma of the prostate: Systemic therapy for a rare disease. Issue 8 (26th March 2023) - Trinh, Jonathan Q.; Lele, Subodh M.; Teply, Benjamin A.
Abstract: Background: Metastatic adenoid cystic (basal cell) carcinoma of the prostate is an exceedingly rare disease entity. As a result, no current consensus exists for optimal systemic therapy. Methods: We present a patient with metastatic adenoid cystic (basal cell) carcinoma of the prostate who subsequently received systemic treatment, including chemotherapy and immunotherapy. We comprehensively reviewed all published data on therapy outcomes in advanced disease. Results: Our patient benefited from combination chemotherapy (carboplatin and paclitaxel), with objective radiographic response and reduction in cancer‐related pain. However, chemotherapy was stopped due to cumulative neurotoxicity, and subsequent immunotherapy with atezolizumab did not produce any response. Our literature review revealed inconsistent outcomes with various treatments but showed most promise with chemotherapy. Targeted therapy and immunotherapy seem to benefit specific cases, and androgen deprivation therapy had minimal evidence of benefit. Conclusion: Based on the findings of our case report and literature review, we suggest platinum‐based chemotherapy doublets as first‐line treatment for metastatic cases of adenoid cystic (basal cell) carcinoma of the prostate, reserving targeted therapy or immunotherapy for select cases based upon molecular profiles.